ARMY AND THE MILITARY PROFESSION IN CONTEMPORARY SOCIETY: CONTRIBUTION TO DEFINING AN ANALYTICAL FRAMEWORK - Milenković, Miloš (The Policy of National Security, 2025)
The social transformations defining contemporary, postmodern, or post-Cold War society have inevitably shaped the military – its organization, functions, role, and societal position. Global shifts from a bipolar to a unipolar and now multipolar geopolitical order demand the continuous evolution of national armed forces. This paper provides an overview of the broader context in which the modern military and military profession operate. It seeks to establish an analytical framework for examining their role and position as a research subject in contemporary society. The objective of this paper is to contribute not only in a hermeneutic (cognitive) sense, but also in a methodological sense by developing an analytical framework based on six key factors: (1) the political system and legislative framework, (2) national culture and social values, (3) historical experience, (4) the economy and the level of technical and technological development (5) the quality of military education and training, and (6) international military cooperation. Each factor is briefly explained, emphasizing its significance and specific characteristics. Through the appropriate selection and application of scientific methods, the proposed analytical framework aims to enable future research on the role and position of the military and the military profession in contemporary society to achieve the most comprehensive scientific understanding of the research subject.